First report of the alien brown alga Scytosiphon dotyi M.J. Wynne (Phaeophyceae, Scytosiphonaceae) in Turkey - TASKIN, E. (Mediterranean Marine Science, 2012)
The alien brown alga Scytosiphon dotyi M.J. Wynne (Phaeophyceae, Scytosiphonaceae) is reported for the first time in Turkey. This species was collected growing epilithically in the midlittoral zone in the Dardanelles (Sea of Marmara, Turkey).